History and / or story of the freedom of the press - Perla-Anaya, José (1994)
The democratic vocation and the search for legality suppose a permanent work for its creation. We are all responsible for their origin and development. More, of course, who have broader responsibilities and powers, public and private. Parliamentarians, judges, the military, the media, the church, citizens in general, international personalities, knew how to act in the other three sister countries studied, in such a way that they developed the new force to persist in their process Search for freedom. A defective change, slow, weak, but that traveled admirably.I continue and will continue to regret that Peru, on the contrary, revealed at the same time conflicts of various kinds, but as urgent as those of our neighbors, its extreme weakness to create and safeguard democracy in democracy or to prevent its rupture.